Exploring effects of a booster workshop on progression and retention of resuscitation skills of residents when added to regular low-dose simulation - Hui-Wen Chen; Hung-Wei Tsai; Yi-Chun Chen; Yu-Jui Chiu; Enoch Yi-No Kang; Yi-Ting Hsu; S. Barry Issenberg; Jen-Chieh Wu (BMC Medical Education)
Abstract Background Improving the resuscitation and teamwork skills of residents is key to better outcomes of in-hospital cardiac arrest events. This study aims to explore the effects of regular low-dose simulation combined with a booster workshop on the progression and retention of resuscitation skills and teamwork among residents. Methods This comparative study took place at a teaching hospital in Northern Taiwan from August 2019 to June 2021. Residents were divided into two groups: the control group received regular low-dose simulation with faculty-led debriefing at the 1st, 6th, and 11th months, while the intervention group participated in an additional 3-hour simulation workshop one week before the 6th-month scenario. The workshop focused on resuscitation and teamwork skills. The study evaluated medical task performance, teamwork, patient safety attitudes, and timing of key resuscitation actions through standardized simulation scenarios, with the assessments occurring at the 1st, 6th, and 11th months (pre-test, mid-test, post-test, respectively). Results Outcome measures in medical task performance and team leader behavior showed statistically significant improvement in both groups (p < 0.05) from pre-test to mid-test. After the intervention, the exposure group demonstrated significantly better results in medical task performance, team leader behavior, patient safety attitudes, and the timing of chest compression initiation compared to the control group (p < 0.05). Five months after the intervention, a significant decline in most measured outcomes was observed in the exposure group (p < 0.05). Despite this decline, the exposure group still performed significantly higher than the control group across most measured outcomes. Conclusions This study demonstrates the potential and advantages of integrating simulation-based training into the clinical training curriculum for residents to improve medical task performance and teamwork behaviors for handling in-hospital cardiac arrest scenarios. The observed decline in skills over time supports the inclusion of regular refresher courses to maintain and advance these vital competencies.